Time Since Migration and HIV Risk Behaviors Among Puerto Ricans Who Inject Drugs in New York City. - Gelpí-Acosta, Camila; Pouget, Enrique R; Reilly, Kathleen H; Hagan, Holly; Neaigus, Alan; Wendel, Travis; Marshall, David M (Substance use & misuse, 2016)
Among people who inject drugs (PWID) in the United States, those who initiated drug injection in Puerto Rico (immigrant Puerto Rican PWID) engage in more injection and sexual risk behaviors, and have higher HIV incidence than non-Hispanic whites.